Plasmid-Controlled Variation in the Content of Methylated Bases in Bacteriophage Lambda Deoxyribonucleic Acid - Hattman, Stanley (1972)
The N(6)-methyladenine (MeAde) and 5-methylcytosine (MeC) contents in deoxyribonucleic acid (DNA) of bacteriophage lambda has been analyzed as a function of host specificity. The following facts have emerged: (i) lambda grown on strains harboring the P1 prophage contain ca. 70 more MeAde residues/DNA molecule than lambda grown either in the P1-sensitive parent, or in a P1 immune-defective lysogen which does not confer P1 modification; (ii) lambda grown on strains harboring the N-3 drug-resistance factor contain ca. 60 more MeC residues/DNA molecule than lambda grown on the parental strain lacking the factor; (iii) lambda grown in Escherichia coli B strains is devoid of MeC, whereas lambda grown in a B (N-3) host contains a high level of MeC; (iv) the MeAde content in lambda DNA is not affected by the N-3 factor. These results suggest that P1 controls an adenine-specific DNA methylase, and that the N-3 plasmid controls a cytosine-specific DNA methylase. The N-3 factor has been observed previously to direct cytosine-specific methylation of phage P22 DNA and E. coli B DNA in vivo; in vitro studies presented here demonstrate this activity.